2020
DOI: 10.1002/acn3.50990
|View full text |Cite
|
Sign up to set email alerts
|

Nonmercaptalbumin as an oxidative stress marker in Parkinson’s and PARK2 disease

Abstract: Objective To investigate the oxidized albumin ratio, which is the redox ratio of human nonmercaptalbumin (HNA) to serum albumin (%HNA), as a biomarker in idiopathic Parkinson’s disease (iPD) and related neurodegenerative disorders. Methods This prospective study enrolled 216 iPD patients, 15 patients with autosomal recessive familial PD due to parkin mutations (PARK2), 30 multiple system atrophy (MSA) patients, 32 progressive nuclear palsy (PSP) patients, and 143 healthy controls. HNA was analyzed using modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Similarly, Rossi et al reported increases in cysteinylation and homocysteinylation of plasma proteins with aging in healthy subjects aged 20-93 [84]. Increases in HNA ratios with aging have been further confirmed in recent studies on patients and healthy controls [32,77]. The rationale for these observations has been attributed to oxidative stress accelerated by aging.…”
Section: Agingmentioning
confidence: 80%
See 1 more Smart Citation
“…Similarly, Rossi et al reported increases in cysteinylation and homocysteinylation of plasma proteins with aging in healthy subjects aged 20-93 [84]. Increases in HNA ratios with aging have been further confirmed in recent studies on patients and healthy controls [32,77]. The rationale for these observations has been attributed to oxidative stress accelerated by aging.…”
Section: Agingmentioning
confidence: 80%
“…These observations were further substantiated by a cohort study on patients with head and neck squamous cell carcinomas, reporting that patients with higher oxidized ALB levels had higher plasma NET levels as well as higher incidences pulmonary cancer metastasis. Another recent study by Ueno et al showed that oxidized serum ALB increased in idiopathic and genetic Parkinson’s diseases [ 77 ]. These authors attributed this to accelerated aging-induced oxidative stress in these patients.…”
Section: Serum Alb Redox State In Pathological Conditionsmentioning
confidence: 99%
“…It is known that in chronic liver and kidney diseases, as well as in diabetes mellitus, the percentage of cysteinylated albumin (Cys34-S-S-Cys) is markedly increased [ 116 ]. In recent years, it has been shown that oxidised albumin can be a biomarker of the severity of such diseases as hyperparathyroidism [ 152 ], acute ischemic stroke [ 153 ], Parkinson’s disease [ 154 ], Alzheimer’s disease [ 155 ], Duchenne muscular dystrophy [ 156 ], etc.…”
Section: Antioxidant Properties Of Albumin: Practical Applicationmentioning
confidence: 99%
“… Okuzumi et al (2019) analyzed serum metabolomics from Parkin patients and age-matched controls, and revealed higher levels of oxidized lipids and fatty acid metabolites and lower levels of antioxidant markers in PARK2 patients, suggesting the relationship between the serum/plasma metabolomics and gene dysfunction. Additionally, as a way of ensuring mitochondrial quality control, the mutation effects the elimination of dysfunctional mitochondria that was associated with an increase of mitochondrial stress, manifesting a systemic oxidative stress markers for the pathomechanisms of Parkin -mutation patients ( Ueno et al, 2020 ).…”
Section: Genetic Metabolomics In Pd Patientsmentioning
confidence: 99%